2022
DOI: 10.1002/cb.2061
|View full text |Cite
|
Sign up to set email alerts
|

Fashion, consumer markets, and democratization

Abstract: Previous research illustrates several attempts that consumers have made to create new markets when marketing organizations have not responded to their desires; however, individual efforts alone are insufficient to assure success in having voices heard. The effectiveness of these efforts heavily depends on the democratization of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Especially, social networking platforms like Facebook, Instagram, TikTok and Twitter (now rebranded as X) offer numerous opportunities for users to establish and present their identities (Zhao et al , 2008; Papacharissi, 2012), ultimately leading to self-presentation behaviors aimed at (re)constructing an image, gaining social recognition or exerting influence on others (Dunne et al , 2010). For instance, users can curate and control their online identities through daily posts of verbal and visual cues, leading others to make assumptions about their lifestyle, appearance, opinions and culture (Boyd, 2015; Atik et al , 2022).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Especially, social networking platforms like Facebook, Instagram, TikTok and Twitter (now rebranded as X) offer numerous opportunities for users to establish and present their identities (Zhao et al , 2008; Papacharissi, 2012), ultimately leading to self-presentation behaviors aimed at (re)constructing an image, gaining social recognition or exerting influence on others (Dunne et al , 2010). For instance, users can curate and control their online identities through daily posts of verbal and visual cues, leading others to make assumptions about their lifestyle, appearance, opinions and culture (Boyd, 2015; Atik et al , 2022).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…SF consumers are “concerned with the effects on the external world around them when they buy, use, and dispose of fashion products” (Jung et al , 2016, p. 485). Thanks to the “logic of sustainability” (Ozdamar-Ertekin et al , 2020) and a new “culture” of fashion (Atik et al , 2022), different fashion paradigms are emerging, giving rise to alternatives to the overconsumption of clothes and fast fashion practices. These changing paradigms stress consumers’: societal and environmental awareness of their economic decisions; emphasis on sustainable materials; respect for craftsmanship and authenticity; and active involvement with the production process (Ozdamar-Ertekin and Atik, 2015, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…With respect to sustainable fashion, Lundblad and Davies' qualitative study revealed that people were inspired to buy green clothing as a way of showcasing their values, expressing themselves, feeling confident and happy, and engaging in environmentally responsible consumption [33]. Social media, as it relates to general fashion and hedonic consumption, also affords consumers diverse benefits in flaunting their personalities and lifestyles, elevating their social status, and connecting with fashion brands that meet their needs [8,34]. SET in this context suggests that sustainable fashion brands might offer assorted benefits (by virtue of being eco-friendly) when using Instagram to communicate with consumers.…”
Section: Social Exchange Theorymentioning
confidence: 99%
“…Despite a growing emphasis on sustainability in the fashion industry, limited research has investigated how sustainable fashion brands can encourage desired consumer behavior on social media [7]. Scholars have called for research on factors that influence sustainable fashion consumption and bolster consumer-brand relationships in a digital context [1,8,9]. Drawing on social exchange theory (SET) [10], this study focuses on benefits of fashion brands that claim sustainability as a crucial aspect.…”
Section: Introductionmentioning
confidence: 99%